2019
DOI: 10.3390/mi10040272
|View full text |Cite
|
Sign up to set email alerts
|

2-Step Drop Impact Analysis of a Miniature Mobile Haptic Actuator Considering High Strain Rate and Damping Effects

Abstract: In recent times, the haptic actuators have been providing users with tactile feedback via vibration for a realistic experience. The vibration spring must be designed thin and small to use a haptic actuator in a smart device. Therefore, considerable interests have been exhibited with respect to the impact characteristics of these springs. However, these springs have been difficult to analyze due to their small size. In this study, drop impact experiments and analyses were performed to examine the damages of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Lee simulated a centrally compressed piezoelectric sensor, whose structure is similar to our accelerometer, but only sensitivity and resonance frequency are analyzed [4]. Choi simulated the drop of a haptic actuator, which possesses spring structure, with 2-step drop analysis of external impact and internal impact [27]. No papers were found to model and simulate the coupling of bolt preload, temperature, and impact in dynamic finite-element analysis.…”
Section: Simulation Modelmentioning
confidence: 99%
“…Lee simulated a centrally compressed piezoelectric sensor, whose structure is similar to our accelerometer, but only sensitivity and resonance frequency are analyzed [4]. Choi simulated the drop of a haptic actuator, which possesses spring structure, with 2-step drop analysis of external impact and internal impact [27]. No papers were found to model and simulate the coupling of bolt preload, temperature, and impact in dynamic finite-element analysis.…”
Section: Simulation Modelmentioning
confidence: 99%
“…(1) Definition and application of Product Fingerprints for new product development and functional characterization. In the field of micro optics, Wang et al [1] presented a study on the development of single composite diffractive optical element for color images generation, and Cao et al [2] worked on the design and fabrication of an artificial compound eye for multi-spectral imaging.In the field of micro mechanical systems and sensors, Díaz Pérez et al [3] presented the development of a one-dimensional control system for a linear motor of a two-dimensional nanopositioning stage, and Choi et al [4] showed how the vibration acceleration can be used as Product Fingerprint on the development of a miniaturized mobile haptic actuator.…”
mentioning
confidence: 99%
“…In the field of micro mechanical systems and sensors, Díaz Pérez et al [3] presented the development of a one-dimensional control system for a linear motor of a two-dimensional nanopositioning stage, and Choi et al [4] showed how the vibration acceleration can be used as Product Fingerprint on the development of a miniaturized mobile haptic actuator.…”
mentioning
confidence: 99%